2012
DOI: 10.1001/archneurol.2011.243
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging in Acute Optic Neuropathies

Abstract: Objective: To evaluate directional diffusivities within the optic nerve in a first event of acute optic neuritis to determine whether decreased axial diffusivity (AD) would predict 6-month visual outcome and optic nerve integrity measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 35 publications
4
46
3
2
Order By: Relevance
“…In this cohort, we observed reduced diffusivity of the ON nerve at the time of the acute inflammatory optic nerve injury, relative to fellow eyes, in agreement with previous studies. [20][21][22] Also consistent with previous studies, 21,22 we observed that diffusivity returned to normal levels with recovery, and there was a near significant association between reduction in diffusivity and visual acuity in ON eyes during the acute phase. Our findings thus confirm the clinical utility of mean diffusivity of the entire optic nerve for the diagnosis and assessment of visual dysfunction caused by ON.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this cohort, we observed reduced diffusivity of the ON nerve at the time of the acute inflammatory optic nerve injury, relative to fellow eyes, in agreement with previous studies. [20][21][22] Also consistent with previous studies, 21,22 we observed that diffusivity returned to normal levels with recovery, and there was a near significant association between reduction in diffusivity and visual acuity in ON eyes during the acute phase. Our findings thus confirm the clinical utility of mean diffusivity of the entire optic nerve for the diagnosis and assessment of visual dysfunction caused by ON.…”
Section: Discussionsupporting
confidence: 91%
“…Axial diffusivity (AD) (i.e., diffusion along the nerve) is reduced in the ON eye during the acute phase (less than 1 month) [19][20][21] and appears to be predictive of visual outcome. 21,22 Thus, DTI may represent a structural marker of axonal integrity, which when applied to ON as a putative model, may provide important insights regarding mechanisms of white matter damage and repair in CNS inflammatory disorders.…”
mentioning
confidence: 99%
“…On the other hand, FA values were reported to be initially normal and then to decrease over time [111,112]. These findings suggest simultaneous demyelination and axonal loss as well as possible reorganization processes to be present in the optic nerve after ON.…”
Section: Optic Nerve Dti In Ms-onmentioning
confidence: 93%
“…Two studies consistently showed initial AD decrease at baseline [112] and after 1 month [111] to predict other visual outcome parameters -i.e. OCT RNFL thinning, full-field VEP latency delay -and visual acuity measures after 6 months [112] as well as OCT RNFL and multifocal VEP changes after 12 months [111]. After an initial decrease, AD values gradually increased back to normal AD values after a median of 18 weeks in MS ON patients.…”
Section: Optic Nerve Dti In Ms-onmentioning
confidence: 97%
“…Diffusion tensor imaging (Figure 3), having relative specificity for pathology affecting axonal and myelin integrity, may also be useful in assessing response to neuro-protective and remyelinating agents [194]. Diffusion tensor imaging may also play a future role in predicting visual outcomes in acute DON; a recent study evaluating 25 patients within 31 days of acute optic neuritis found that decreased axial diffusivity was associated with a worse 6-month visual outcome and correlated with VEP and RNFL measures of axon and myelin injury [195]. The ability to better characterize axonal loss and predict visual outcomes in DON has the potential to better inform acute management decisions and the determination of which patients would benefit from early initiation of therapies aimed at preventing the development of MS and MS-associated disability.…”
Section: Future Perspectivementioning
confidence: 99%